Review of Green Supply Chain Processes. Issue 3 (2015) - Kumar, Niraj; Agrahari, Ravi P.; Roy, Debjit
Abstract: In the last few decades, environmental concerns of manufacturing operations have motivated the organisations to implement green principles in different processes of the supply chain. In this paper, literature in green processes is critically reviewed to understand the process-specific green issues of the supply chain. A 10-year period (2005-2014) is considered in this paper to select and analyse relevant studies. Using related keywords, we found 299 papers, out of which 66 are discussed in this review paper. We have excluded papers pertaining to areas such as paper industry, textile industry, and municipal waste management. Moreover, the paper focuses on studies conducted to improve the greenness of different supply chain processes and to identify the barriers in adopting these green practices.